Functional genomics reveal gene regulatory mechanisms underlying schizophrenia risk - Yongxia Huo (Nature Portfolio, 2019)
We know a large number of risk SNPs for schizophrenia, but little about how these SNPs contribute to the disorder. Here, the authors use functional genomics to identify risk SNPs that disrupt transcription factor binding and validate the regulatory effects of the transcription factor binding-disrupting SNPs.